INNOVATIVE APPROACHES TO THE USE OF PASSIVE SOLAR HEATING SYSTEMS TO IMPROVE THE ENERGY EFFICIENCY OF AGRICULTURAL BUILDINGS AND STRUCTURES - Sadykov, Zhamal; Fayziev, Tulkun; Khamraev, Tolib; Xidirov, Mirabbos (Innovatsion texnologiyalar, 2024)
Currently, in world practice, scientific research and design work is being carried out on the development and creation of passive solar heating systems. If the heat storage wall of a passive solar heating system consists of a perforated heat storage wall, then such a wall simultaneously transfers heat into the room and supplies warm fresh air. As a result, warm, fresh air enters the room, and heat losses are reduced by reducing the temperature of the blackened outer surface of the heataccumulating wall. The calculation methods and theoretical studies of passive systems are very complex, which makes it difficult to justify the design of structures with such systems. In this regard, the task of creating simple approximation methods for calculating the integral characteristics of passive solar heating systems of buildings and structures for the heating season as a whole is gaining practical interest, such characteristics as the heating load replacement coefficient, which determines both the technical and economic indicators of such systems. Theoretical research and calculations show that a slight addition of metal fibers to a poor heat conductor greatly increases its thermal conductivity and practically does not change its volumetric heat capacity. To increase the heat transfer capacity of the heat storage wall is the use of a perforated heat storage wall, which make it possible to increase the intensity of heat removal from the surface of the heataccumulating wall during the period of insolation.. In passive solar heating systems, it is advantageous to use a more thermally conductive material for the heat storage wall The perforated heat-accumulating wall and air supply through it help to increase the effect of heat transfer into the depth of the wall and into the room.